Application of Antifreeze Substances in Food Cryopreservation - Mengxia Wu; Qin Xu; Han Ding; Dumin Zhao; Ying Wang; Baocai Xu (Foods, 2025)
Freezing is a crucial technology for preserving food quality and extending shelf life. However, frozen storage often leads to protein oxidation, degradation, and cellular structural damage, compromising food palatability. To address these challenges, antifreeze substances have emerged as a promising solution. This review comprehensively summarizes the current research on antifreeze substances, including natural compounds and artificial analogs. For natural antifreeze substances, the mechanisms of antifreeze proteins (AFPs), antifreeze peptides (AFPPs), antifreeze polysaccharides (AFPLs), and antifreeze phosphates (AFPSs) are elucidated. Additionally, the preparation of artificial synthesis analogs and the application of antifreeze substances are discussed. By presenting their properties and research advancements, this review aims to provide a reference for the practical utilization of antifreeze substances in food-freezing applications.